Legal Implications of the Use of Artificial Intelligence in the Business World in Indonesia - Muhammad Aldo; Muhammad Ranu Al Habib; Dedy Lazuaardi; Ayunda; Armin Nasution (Lex Progresiva, 2025)
This study examines the legal implications of the use of artificial intelligence (AI) in the Indonesian business world, which is experiencing rapid development in line with the national digital transformation. AI has been widely used in various industrial sectors to improve efficiency and service quality. However, behind its benefits, significant legal challenges arise, particularly related to regulation, legal accountability, personal data protection, and the ethics of technology use. This study uses qualitative and quantitative approaches with normative and empirical juridical methods, supported by statistical analysis of multiple linear regression, t-test, F-test, normality test, and coefficient of determination. Data were obtained from 100 respondents consisting of business actors, academics, and legal practitioners experienced in the use of AI in the business sector. The results show that the variables of legal regulation, ethics and data security, and business actors’ understanding of AI significantly influence perceptions of the legal implications of AI use. The coefficient of determination of 57% indicates that these three variables are able to explain a large portion of the variation in legal risks faced by business actors. This study concludes that Indonesia needs a clearer, more adaptive, and proactive legal framework to regulate the use of AI, in order to create a safe and sustainable business climate without stifling innovation. These findings are expected to form the basis for formulating more comprehensive policies in regulating smart technology in the digital economy sector.